2022
DOI: 10.1016/j.jand.2021.08.100
|View full text |Cite
|
Sign up to set email alerts
|

“Come with us for a week, for a month, and see how much food lasts for you:” A Qualitative Exploration of Food Insecurity in East Harlem, New York City

Abstract: Background Food insecurity refers to uncertain access to food on a consistent basis and the stress experienced by families who worry about having sufficient resources to provide balanced meals in their households. Food insecurity has a disproportionate influence on people of color. A robust body of evidence links food insecurity to poor health outcomes.Objective To document experiences of food insecurity among linguistically and ethnically diverse residents of the East Harlem neighborhood of New York City by e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
3
6
0
Order By: Relevance
“…Consistent with prior literature, people in this study also exhibited food resourcefulness and cooking knowledge to overcome barriers presented by social infrastructures [ 13 , 45 , 46 , 49 ]. Those experiencing food security, in particular, demonstrated food agency (an improved ability to acquire and prepare food to meet their household food needs) through their use of available resources (for example, food budgeting) and skills (for example, stretching leftovers) compared with people experiencing food insecurity [ 50 ].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Consistent with prior literature, people in this study also exhibited food resourcefulness and cooking knowledge to overcome barriers presented by social infrastructures [ 13 , 45 , 46 , 49 ]. Those experiencing food security, in particular, demonstrated food agency (an improved ability to acquire and prepare food to meet their household food needs) through their use of available resources (for example, food budgeting) and skills (for example, stretching leftovers) compared with people experiencing food insecurity [ 50 ].…”
Section: Discussionsupporting
confidence: 86%
“…This inequity was illustrated in reflections of our study participants who described the lack of access to fresh foods in their community despite the demand being present. Instead, people described an overabundance of fast-food outlets, corner stores, and liquor stores, which is consistent with literature focused on food insecurity and food environments in other urban areas [ 13 , 45 , 46 ].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Food services were also limited in quantity of food provided and the number of nutritious, palatable options (Gany et al, 2013 ). To manage experiences of food insecurity, East Harlem residents carefully managed food spending, dedicated substantial time to visiting stores and accessing food pantries, and relied on a cycle of public benefits (i.e., cash assistance and SNAP) that left many without sufficient financial resources by the end of each month (Nieves et al, 2021 ). Food pantry services may be greatly improved through the coordination of public agencies to influence the food system and advocate for local policies, including neighborhood zoning and labor regulations, to improve food access (Cohen & Ilieva, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Carney and Krause show through qualitative case studies that language access and immigration status are important determinants of food access for Mexican and Central American migrants in Santa Barbara county 21 . An in-depth qualitative study of adults living in East Harlem demonstrated that many Spanish-and Chinese-speaking adults' shopping patterns were dictated by shopping at stores where food was cheapest or where the grocer spoke their language 22 . https://doi.org/10.1017/S1368980023000575 Published online by Cambridge University Press…”
Section: §2 Transportation and Language Access As Social Determinants...mentioning
confidence: 99%